Dysbiosis Across Multiple Body Sites in Critically Ill Adult Surgical Patients. Issue 6 (December 2016) - Yeh, Andrew; Rogers, Matthew Brian; Firek, Brian; Neal, Matthew D.; Zuckerbraun, Brian S.; Morowitz, Michael J.
Abstract : ABSTRACT: The microbiota of critically ill patients likely undergoes dramatic changes but has not been rigorously studied with a culture-independent high-throughput approach. The aim of this study was to characterize spatial and temporal variation in the microbiota of critically ill patients. Trauma and acute surgery patients admitted to the intensive care unit (ICU) were sampled at five body sites (stool, tongue, skin, trachea, urine) every 3 to 4 days. A mean of 10.8 samples was collected from 32 patients with a mean sampling period of 8.8 days. Bacterial 16S rRNA sequences were amplified and sequenced for microbiota analyses. Results were compared to data from unhospitalized adult participants in the American Gut and Human Microbiome Projects. Relative to healthy adults, alpha diversity was decreased in ICU gut and skin samples at all time points. Diversity in tongue swabs decreased over time. Beta diversity measures indicated differences in community membership between critically ill and healthy adults at each body site. Taxonomic alterations in the ICU included depletion of important commensal bacteria such as Faecalibacterium in GI samples and Corynebacterium in skin swabs and enrichment with pathogens such as Enterococcus, Mycoplasma, and Staphylococcus . A high proportion of ICU sample sets contained pathogens present simultaneously at three body sites indicating widespread colonization. In several cases, clinically relevant airway infections were preceded by the appearance of the causative pathogen in tracheal microbiome profiles. These results demonstrate that the microbiome of critically ill patients undergoes a loss of diversity, loss of site specificity, and a shift toward dominant pathogens. These changes may provide opportunities to precisely modulate the microbiome and thereby improve patient outcomes. Abstract : Supplemental Digital Content is available in the text